2016
DOI: 10.1111/ipd.12229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral clinical problems on oral health‐related quality of life in brazilian children: a hierarchical approach

Abstract: The clinical and perceived conditions of oral health in Brazilian 12-year-olds were associated with a negative impact on oral health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
(36 reference statements)
6
18
0
Order By: Relevance
“…This is supported by our ndings which revealed, even after adjustment in the multivariate analysis, a highly signi cant association found between the lowest family income tertile and OHRQoL. Similar ndings have been reported in other studies among children in Brazil and India [26,35,36]. It is therefore important to assess socio economic conditions in general when dealing with OHRQoL, even among school children who are eligible for free hospital dental services in Sri Lanka.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is supported by our ndings which revealed, even after adjustment in the multivariate analysis, a highly signi cant association found between the lowest family income tertile and OHRQoL. Similar ndings have been reported in other studies among children in Brazil and India [26,35,36]. It is therefore important to assess socio economic conditions in general when dealing with OHRQoL, even among school children who are eligible for free hospital dental services in Sri Lanka.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have revealed that malocclusion plays an important role in social interactions and psychological well-being in adolescents [15,35,39] and it has been suggested that there is a signi cant impact of malocclusion on the OHRQoL of young children. Our ndings con rm this and show a strong signi cant positive association between anomaly and the OIDP score after adjustment for other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The self‐reported need represents the degree of discomfort that the presence of dental problems causes in the daily lives of the children. Social inequalities have been identified in the impact of oral conditions in the children's daily activities in Brazil. Moreover, they may be determinant for seeking dental care or not, and may explain some of the resulting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Caries lesions may compromise oral functions and impact negatively on the quality of life [Souza et al, 2017]. Although both types of lesions are caused by the same determinants (biofilm formation and frequency of sugar ingestion), the different characteristics of the tissues modulate their progression, with a faster development of root caries [Nyvad and Fejerskov, 1982].…”
Section: Discussionmentioning
confidence: 99%